-3+10y+6=15+12y-18

To follow the instructions:

-3+6 +10y = 15 - 18 +12y

3+10y=-3+12y

Now collect the 'y' terms on the left:

10y - 12y = -3 - 3

-2y = -6

y=`(-6)/(-2)`

**y=3**

By collecting the y terms on the right hand side, the result will be the same but it may appear easier because you will not have to worry about negative symbols which can sometimes confuse the answer.

The like terms on each side have been collected and so we can proceed from that point:

3+10y=-3+12y

Now move the y terms to the right thus:

3+3 = 12y -10y

6=2y

`6/2 =y`

3=y

`therefore y=3`

**therefore y=3 and it seems easier to collect the y yerms on the
right to avoid confusion with negative symbols.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.